Low-dose cisplatin causes growth inhibition and loss of autophagy of rat astrocytes in vitro. (24th August 2018) - Jiang, Nan; Meng, Chengjie; Han, Xiao; Guo, Jun; Li, Haoming; Yu, Zhengquan
Highlights: Low-dose CDDP inhibits proliferation and induces loss of autophagy in cultured rat astrocytes. CDDP suppressed autophagic function by lessening the levels of autophagy-related molecules, especially the formation of LC3-II. A low dose of CDDP induced delayed cell death. Abstract: Astrocytes are the most abundant cell type in the central nervous system. Defects in astrocyte function have been implicated in a variety of diseases. Cisplatin (CDDP) is a chemotherapeutic drug that is widely used to treat various cancers. However, it causes neurocognitive impairment in patients. Little is known about the damaging effects of chemotherapeutic drugs like CDDP on astrocytes. Presently, we found that a low dose of CDDP distinctly inhibited astrocyte proliferation and induced delayed cell death. Additionally, the same low dose of CDDP suppressed the expression of autophagy-related molecules including LC3-II, SQSTM1/P62, ATG5, and ATG7. However, except for LC3-II, expression of the molecules recovered when the cells were subsequently cultured in CDDP-free medium. Analysis of autophagic flux using Ad-mRFP-GFP-LC3 transfection revealed reduced numbers of autophagosome and autolysosome puncta in low-dose CDDP-treated cells. These results indicate that the low-dose CDDP inhibited astrocyte growth and autophagy, the central nervous system cytotoxicity induced by CDDP needs to be further explored.